2021
DOI: 10.7759/cureus.20832
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Job Syndrome With Autism: Complicated With Hidradenitis Suppurativa and Chronic Deep Vein Thrombosis

Abstract: Job syndrome or hyper-immunoglobulin E syndrome is one of the rare immunologic diseases with only about 300 cases described in the literature until now. Given their low prevalence, our understanding of both autosomal dominant and recessive Job syndromes is still evolving. No specific treatment options are available but early diagnosis may help in treating cases prophylactically with antibiotics and wound care to reduce the patient's burden. We recently encountered a patient diagnosed with Job syndrome with aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…Most authors agree that HS is a debilitating disorder characterized by chronic inflammation in intertriginous areas with an often-unsatisfactory response to treatment [ 59 ]. Based on our observations, a phenomenon that worsens the prognosis further is the late diagnosis, which was confirmed by the work of Howdhury et al [ 60 ], who pointed out the small number of cases described in the literature. Additionally, the research team of Howdhury found it necessary to establish a proper treatment plan for the disease [ 60 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most authors agree that HS is a debilitating disorder characterized by chronic inflammation in intertriginous areas with an often-unsatisfactory response to treatment [ 59 ]. Based on our observations, a phenomenon that worsens the prognosis further is the late diagnosis, which was confirmed by the work of Howdhury et al [ 60 ], who pointed out the small number of cases described in the literature. Additionally, the research team of Howdhury found it necessary to establish a proper treatment plan for the disease [ 60 ].…”
Section: Discussionsupporting
confidence: 87%
“…Based on our observations, a phenomenon that worsens the prognosis further is the late diagnosis, which was confirmed by the work of Howdhury et al [ 60 ], who pointed out the small number of cases described in the literature. Additionally, the research team of Howdhury found it necessary to establish a proper treatment plan for the disease [ 60 ]. According to other studies, it is probably even more important to attempt to understand the pathomechanisms of the disease, which would make healthcare providers and patients more aware of HS-associated risks and allow for the introduction of an appropriate treatment scheme [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation